2021
DOI: 10.3390/ani11113132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Medical Zinc Oxide with Different Ratios of Inorganic: Organic Zinc or Reducing Crude Protein Diet with Mixed Feed Additives in Weaned Piglet Diets

Abstract: One hundred twenty weaned piglets (9.34 ± 0.74 kg) were used in a four-week experiment to investigate the effects of replacing medical ZnO with a different ratio of inorganic and organic zinc (IZ:OZ) or a low-crude-protein diet (LP) with mixed feed additives (MFAs) in the weaned piglets’ diet. The dietary treatments included a control (CON), T1 (T1; ZnO 1000 mg/kg), T2 (IZ:OZ 850:150), T3 (IZ:OZ 700:300), T4 (IZ:OZ, 500:500), and T5 (LP with MFAs (0.1% essential oils + 0.08% protease + 0.02% xylanase)). The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…It could also indicate that the lower level of ZnO, compared with the pharmaceutical level, exacerbated the negative impacts of F18 + E. coli challenge on growth of nursery pigs. However, there is limited information about the negative impacts of the low level of ZnO in nursery feeds, and previous studies have shown inconsistency in the dose response of ZnO to growth performance and other variables of interest in nursery pigs ( Pieper et al, 2012 ; Upadhaya et al, 2018 ; Oh et al, 2021 ; Hansen et al, 2022 ). The pharmaceutical use of ZnO has been known as having a strong effect on preventing post weaning diarrhea and promoting the growth of nursery pigs ( Kim et al, 2019 ), but the underlying properties or the mode of action of ZnO are still not well-determined by dose response.…”
Section: Discussionmentioning
confidence: 99%
“…It could also indicate that the lower level of ZnO, compared with the pharmaceutical level, exacerbated the negative impacts of F18 + E. coli challenge on growth of nursery pigs. However, there is limited information about the negative impacts of the low level of ZnO in nursery feeds, and previous studies have shown inconsistency in the dose response of ZnO to growth performance and other variables of interest in nursery pigs ( Pieper et al, 2012 ; Upadhaya et al, 2018 ; Oh et al, 2021 ; Hansen et al, 2022 ). The pharmaceutical use of ZnO has been known as having a strong effect on preventing post weaning diarrhea and promoting the growth of nursery pigs ( Kim et al, 2019 ), but the underlying properties or the mode of action of ZnO are still not well-determined by dose response.…”
Section: Discussionmentioning
confidence: 99%
“…Castillo et al reported that the combined addition of MOS and organic zinc could improve the feed conversion efficiency of piglets in the first two weeks after weaning [ 25 ]. Studies found that adding MOS-rich yeast products (yeast or yeast enzymolysate) and ZnO to the diet improved the growth performance and immune function of weaned piglets [ 10 , 26 ]. Similar to the results of this study, low doses of ZnO (1000–1500 mg Zn/kg) [ 10 , 21 ], and even lower doses of coated ZnO (500 mg Zn/kg) also improved the growth performance of piglets [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that adding MOS-rich yeast products (yeast or yeast enzymolysate) and ZnO to the diet improved the growth performance and immune function of weaned piglets [ 10 , 26 ]. Similar to the results of this study, low doses of ZnO (1000–1500 mg Zn/kg) [ 10 , 21 ], and even lower doses of coated ZnO (500 mg Zn/kg) also improved the growth performance of piglets [ 27 ]. However, some studies reported that 1600 mg Zn/kg ZnO failed to promote growth performance in piglets [ 12 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the weaning period, piglets face new environments and experience intestinal morphological changes because of solid diet feeding ( 13 ). Post-weaning diarrhea (PWD) caused by these stress factors can lead to changes in gastrointestinal microbiology and immunology ( 14 ).…”
Section: Introductionmentioning
confidence: 99%